2019
DOI: 10.1186/s12909-019-1756-y
|View full text |Cite
|
Sign up to set email alerts
|

Resident-led organizational initiatives to reduce burnout and improve wellness

Abstract: BackgroundProfessional burnout among medical trainees has been identified as a national concern in need of attention. A significant challenge for residency programs is designing and implementing effective strategies to promote resident wellness and reduce burnout. Emerging evidence highlights the importance of developing organizational changes targeting physician burnout.MethodsTo address this critical need, Harvard South Shore (HSS) Psychiatry Residency Training Program aimed to assess burnout among residents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 29 publications
0
41
0
Order By: Relevance
“…A study conducted in 2013 by Kathleen A et al (48) reported the annual attrition rate in pediatrics as 2.9%, which was found to be much lesser compared to other specialties i.e., General surgery (5.1%), Family medicine (4.7%), Anesthesiology (3.6%), Psychiatry (7.9%), and Obstetrics and Gynecology (4.2%). Other studies (17,21,23,49) have also depicted a lower average attrition score. This would suggest that an intervention was highly needed in our program to bring down the attrition rate, and indeed after applying all changes focusing on wellness using the TOC model, the average attrition rate came down to a shocking 1.75%.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A study conducted in 2013 by Kathleen A et al (48) reported the annual attrition rate in pediatrics as 2.9%, which was found to be much lesser compared to other specialties i.e., General surgery (5.1%), Family medicine (4.7%), Anesthesiology (3.6%), Psychiatry (7.9%), and Obstetrics and Gynecology (4.2%). Other studies (17,21,23,49) have also depicted a lower average attrition score. This would suggest that an intervention was highly needed in our program to bring down the attrition rate, and indeed after applying all changes focusing on wellness using the TOC model, the average attrition rate came down to a shocking 1.75%.…”
Section: Discussionmentioning
confidence: 89%
“…A literature review was done through Google Scholar and PubMed, and several articles related to the process of initiating a wellness program were identi ed. One such study described that achieving resident wellness is a signi cant challenge, and to implement effective strategies resident-led continuous feedback and leadership cooperation is a must (21). A collection of ample literature on wellness depicted strategies for identifying the problem in the program and individual system-level interventions have shown improvement in resident wellness (22).…”
Section: Literature Review/frameworkmentioning
confidence: 99%
“…10,11,40 These have generally focused on individual wellness and include mindfulness, journaling, self-reflection, stress management, and gratitude activities. 7 While these do provide potential skills for trainees to use throughout their careers, so far these individual approaches have only met with marginal success. Additionally exercises such as mindfulness are likely to frustrate those who recognize and are returned to dysfunctional environments that contribute to impaired wellness.…”
Section: Challenges With Wellnessmentioning
confidence: 99%
“…Burnout in medicine is reported in many studies to be above 40-60%, which has been the primary driver of this intense focus. [3][4][5][6][7] There have been several articles suggesting methods for changing our educational settings to impact what some have called an "epidemic" of burnout. 8,9 Interventions have included mindfulness training, guided reflection, wellness days, art therapy, and gratitude exercises.…”
Section: Introductionmentioning
confidence: 99%
“…12 This is despite numerous emerging positive personal and professional impacts on resident trainees who engage with such programming. 13 Our appeal is therefore simple, whether during the COVID-19 pandemic or afterward: develop opportunities for resident physicians to participate in art-making or viewing, be it through writing, photography, drawing, or music. Empower trainees to share their work and reflect upon it.…”
mentioning
confidence: 99%